North Atlantic Regional Water Resources Study. Appendix E. Flood Damage Reduction and Water Management for Major Rivers and Coastal Areas. - CORPS OF ENGINEERS NEW YORK NORTH ATLANTIC DIV (1972)
The purpose of Appendix E is to define the magnitude of the present and projected flood threat on the main stem rivers, major tributaries and coastal areas of the North Atlantic Region; to evaluate potential programs for flood damage reduction; and to describe various aspects of, and the potential for, water management to increase the supply of water for projected future withdrawal and instream water needs. The information and data developed serve as inputs to Appendix T, Plan Formulation. Appendix E to report dated Jun 72, AD-A036 616. See also Appendix F, AD-A036 627. Contains envelope with 2 maps.